Comparative analysis of the Global Initiative for Asthma and the South American guidelines for the diagnosis, management and prevention of asthma in pediatric patients - Leonardo Villegas Huertas; Mikel Silva Barrios; Jean Pierre Seguier Huamán; José Vela Ruiz; Joyce Desposorio Robles; Maria del Socorro Alatrista Gutiérrez (Medisur, 2023)
Foundation: Asthma is a chronic inflammatory disease with a high prevalence in South America, which requires proper diagnosis, optimal management and prevention measures supported by constantly updated scientific evidence. Objective: to carry out a comparative analysis between the Global Initiative for Asthma and the South American guidelines for the diagnosis, management and prevention of asthma in pediatric patients. Methods: descriptive observational study that compares the 2023 Global Initiative for Asthma guideline with national guidelines from the South American countries Colombia, Argentina, Chile, Uruguay, Venezuela and Peru, in the following parameters: diagnostic recommendations, management recommendations and prevention strategies. Results: differences were found in prevention and education recommendations in the guides analyzed, while the Global Initiative for Asthma and some South American guides mention prevention measures, other guides do not mention them or have limited information in this regard. In auxiliary tests, all guidelines mention performing spirometry to evaluate lung function, but there are differences with the inclusion of other tests, such as the allergy test or the measurement of exhaled nitric oxide. Conclusions: Greater standardization and updating of South American guidelines is required to guarantee adequate and consistent management of asthma in the region.